Management Outcomes of Lymphadenopathy among the Children - Yahya Salim, Siamand; Amjad Boya Kaka , Wesam (Diyala Journal of Medicine, 2023)
Background: Lymphadenopathy refers to the enlargement of lymph nodes due to various causes, and its appropriate management is crucial for optimal patient outcomes. Objective: To analyze the onset of lymphadenopathy (LAP) in children in terms of gender and age, explore its clinical manifestations and the specific lymph node areas affected, identify prevalent causes, and assess the outcomes of various treatment approaches. Patients and Methods: This cross-sectional study conducted between October 2021 and March 2023 at Rapareen Teaching Hospital for Children in Erbil City, which examined the lymphadenopathy in 40 children . The study included children aged 0-15 years with a lymphadenopathy diagnosis. Data collection involved recording demographic information, lymphadenopathy site and characteristics, clinical symptoms, antibiotic usage and response, reactive diagnoses, and treatment outcomes. Additional laboratory measurements were also taken. The collected data were analyzed using descriptive statistics, statistical tests, and logistic regression analysis. The study adhered to ethical principles, obtained informed consent, and ensured data confidentiality. Results: The mean age of the children was 3.397 ± (2.192) years. 23 (59%) children had a single lymphadenopathy, and 16 (41%) had multiple lymphadenopathies. The most common site of lymphadenopathy with a frequency of 10 (25%) was in the posterior cervical region, while 7 (17.5%) was observed in the submental area. 38 (95%) children received antibiotic treatment. Out of this number, 23 (60.5%) responded positively to the treatment, while 15 (39.5.5%) did not respond. Conclusion: The results of this study showed that in the patients who were treated with antibiotics, the drug was able to lead to some degree of recovery.